Analisis Fenomenologi Tradisi Umbawa Gandang Langngan Tanete Di Lembang Ratte, Kec.Masanda - Fani Patuden; Srirejeki Allu Parante; Barto Barto; Herdi Herdi; Resi Bura Tasik (Universitas Katolik Widya Karya Malang, 2023)
Umbawa gandang langngan tanete is a unique tradition in the Toraja area, to be precise, in Lembang Ratte, Masanda District. This tradition is said to be unique because in the Toraja area it is only found in the Masanda area. The umbawa gandang langngan tanete tradition is one of the last forms of respect for the Ma'dika people who have died. The purpose of this study was to analyze phenomenologically the tradition of the umbawa gandang langngan tanete by using a qualitative descriptive research method with interview techniques with informants to obtain data related to the facts found in the research process of the umbawa gandang langngan tanete tradition in Lembang Ratte. . After researching the umbawa gandang langgan aunttete, the results found by the researchers were that there was a unique tradition that was applied to the Ma'dika people in Lembang Ratte Kec. Masanda who carried out a series of Ramnbu Solo ceremonies, namely umbawa gandang langngan tanete. The following is a series of activities carried out in this tradition, namely using torches to light the way when going up the mountain at night or coming down from the mountain. drums are sounded up to the top of the mountain or down to the beat with a regulated beat, cutting animals such as pigs and buffalo whose meat cannot be eaten by the family of the deceased, worshiping, ma'badong, placing a torch on the door of the funeral home whose smoke then rises into the sky.